Liver resection in elderly patients with extensive CRLM: Are we offering an adequate treatment? A propensity score matched analysis. Issue 6 (June 2022) - Di Martino, Marcello; Dorcaratto, Dimitri; Primavesi, Florian; Syn, Nicholas; Blanco-Terés, Lara; Dupré, Aurélien; Piardi, Tullio; Rhaiem, Rami; Fernández, Gerardo Blanco; De Armas Conde, Noelia; Rodríguez Sanjuán, Juan Carlos; Santiago, Roberto Fernández; et al.
Abstract: Background: Data on the management of elderly patients with extensive colorectal liver metastases (CRLM) are scarce and conflicting. This study assesses differences in management and long-term oncological outcomes between older and younger patients with CRLM and a high Tumour Burden Score (TBS). Methods: International multicentre retrospective study on patients with CRLM and a category 3 TBS, submitted to liver resection. Patients were divided into two groups according to their age (younger and older than 75) and were compared using propensity score matching (PSM) analysis and multivariable regression models. Differences in management and oncological outcomes including recurrence-free survival (RFS) and overall survival (OS) were assessed. Results: The study included 386 patients, median follow-up was 48 months. The unmatched comparison revealed a higher ASA score (p = 0.035), less synchronous CRLM (47% vs 68%, p = 0.003), a lower median number of lesions (1 vs 3, p = 0.004) and less perioperative chemotherapy (CTx) (66% vs 88%, p < 0.001) in the elderly group. Despite the absence of CTx being an independent predictor of decreased RFS and OS (HR 0.760, p = 0.044 and HR 0.719, p = 0.049, respectively), the elderly group still received less CTx (OR 0.317, p = 0.001) than the younger group. After PSM (n = 100 patients), the two groups were comparable, however, CTx administration was still significantly lower in the elderly group. Conclusion: Liver resection should be considered in patients aged 75 and older, even if they present with extensive liver disease. Despite CTx being associated with improved oncological outcomes, a large percentage of elderly patients with CRLM are undertreated.